Eucheumatopsis isiformis gen. & comb. nov. (Solieriaceae, Rhodophyta) from the Yucatan Peninsula, to accommodate Eucheuma isiforme. Issue 1 (2nd January 2019) - Núñez-Resendiz, María Luisa; Dreckmann, Kurt M.; Sentíes, Abel; Wynne, Michael J.; León-Tejera, Hilda P.
ABSTRACT: On the basis of COI-5P, cox 2–3 spacer, RuBisCo spacer, and rbc L sequences, Eucheuma was resolved as a paraphyletic genus in the Solieriaceae. Specimens of E. isiforme from the Yucatan Peninsula and Florida form an independent lineage in the family that was also different from E. denticulatum, the generitype. To accommodate this species, we described Eucheumatopsis as a new genus that differs from Eucheuma both molecularly and geographically. Because the four molecular markers used and morphological characters did not support the independence of Eucheuma isiforme var. denudatum from E. isiforme var. isiforme, we have proposed to no longer recognize var. denudatum as a separate variety.